Predicting consumers' intention to shop online in an emerging market: A COVID-19 perspective - Md. Afsarul Islam; Nishath Anjum; Md. Imran Ahmed (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2021)
As an emerging economy, Bangladesh has witnessed a remarkable development in adopting information and communication technologies over the last decade. Hence, the fi eld of e-commerce is expanding rapidly and consumers are now using the internet as an alternative channel for buying. The fundamental purpose of this study is to predict consumers' intention to purchase online during the COVID-19 pandemic in Bangladesh. Based on the Theory of Planned Behavior (TPB), this study attempts to explore certain factors (attitude towards online shopping, subjective norms, perceived behavioral control) aff ecting consumers' online buying intention. A structured questionnaire has been used to collect the primary data through the CAWI survey method. A total of 157 respondents have participated in this study from diff erent universities in Sylhet city, Bangladesh. This study employed multiple regression analysis to test the proposed research model. The fi ndings indicate that all the predictors have a signifi cant impact on consumers' behavioral intention to do online shopping during the COVID-19 pandemic. However, any developing country like Bangladesh has a genuine need for more research works on the e-commerce fi eld. This study provides some valuable insights into the adoption of the online shopping system in an emerging economy which helps the e-commerce industry to understand online consumers' behavior to develop various marketing strategies accordingly. The study also contributes to the body of knowledge both at the academic and practical levels.
Keywords: M30; M31; M37; 650; online shopping; purchase intention; theory of planned behaviour (TPB); consumers; emerging market; COVID-19